Analisis Gaya Mengajar Guru Matematika Terhadap Motivasi Belajar Siswa - Susilawati, Susi; Ita Yusritawati; Manjaniawati, Suchi; Florenza, Florenza (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to describe the teaching style of mathematics teachers in relation to the learning motivation of class XI students at SMA Negeri 1 Cigugur, Kuningan Regency. This research use desciptive qualitative approach. The subject of this research is the teaching style of mathematics teachers and student learning motivation. Data collection techniques include observation, interviews and questionnaire. Data analysis techniques using the Miles & Huberman model include data collection, data reduction, data presentation and drawing conclusions. Test data accuracy with a triangulation test consisting of data source triangulation, technical triangulation and time triangulation. The results of this research indicate that there is a relationship between teacher teaching style and student learning motivation. During the learning process, teachers use collaboration or a combination of teaching styles. Classical teaching style, technology teaching style, personal teaching style and interactive teaching style are used as teaching styles. Of the four teaching styles, teachers combine them in the learning process, where teachers try to adapt to students' needs during teaching and learning, so that the learning process runs smoothly and can generate motivation in students